Digging Wells, Divining a Curriculum of Hope in Slipping Fidelities - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2020)
Joanna Macy (2009) suggests that a shift toward a life-sustaining civilization includes reassessing values and relooking at perceptions of reality. In this editorial, the metaphor of divining is used to explain the creation of hope in the grief-filled epoque of the Chthulucene. Authors in this issue collectively ask: How do we live together? How do we see the world? How do we make meaning? How do we tell truths? How do we make a better world? Imagination is the self and the world merging and emerging, entanglements of making that challenge our commitments and obligations as researchers. As we conduct research, we are constructing new life worlds, dreaming and shaping futures. In this editorial, I’m thinking about hope, of metaphorically digging wells, committing to the difficult work of moving through layers of barriers toward the originary whys, and knowing there are multiple truths and needs. In this process we can come to places of relation, understanding, self- and world-healing.